Pemanfaatan Aplikasi Phyphox untuk Menentukan Percepatan Gravitasi Bumi dan Mengukur Penguasaan Konsep Siswa SMA - Rosynanda Nur Fuziah; Andri Suryana; Hasbullah Hasbullah; Kristiyanto Kristiyanto (CV. ALIM'SPUBLISHING, 2026)
The main issue in physics learning is the limited use of digital technology that can support simple experiments in a practical and accurate way. One innovative effort to address this challenge is the use of the Phyphox application on smartphones to conduct experiments in determining the acceleration due to gravity through the concept of a simple pendulum. This study aims to investigate the effectiveness of using Phyphox in measuring ggg as well as improving students’ mastery of kinematics concepts. The research employed a quasi-experimental approach with a pretest–posttest control group design. The sample consisted of two eleventh-grade classes selected purposively: the experimental class using Phyphox-based learning and the control class using conventional methods. Research instruments included experimental devices (smartphone with Phyphox, simple pendulum, measuring tape, and stand), learning achievement tests (pretest and posttest), student response questionnaires, and observation sheets. Data were analyzed using t-tests, N-gain calculations, and descriptive analysis. The results showed that the average measured values of ggg were close to the theoretical value of 9.8 m/s², with measurements obtained using pendulum lengths of 40 cm, 50 cm, and 60 cm. Student learning outcomes in the experimental class improved significantly, with a higher gain compared to the control class. In addition, student responses were positive, as indicated by increased motivation, understanding, and learning satisfaction. Phyphox is effective as a physics learning medium for simple experiments, as it provides representative measurement results while enhancing students’ conceptual mastery and engagement in learning.